Genome-Scale Evolution: Reconstructing Gene Orders in the Ancestral Species - Bourque, Guillaume (Cold Spring Harbor Laboratory Press, 2002)
Recent progress in genome-scale sequencing and comparative mapping raises new challenges in studies of genome rearrangements. Although the pairwise genome rearrangement problem is well-studied, algorithms for reconstructing rearrangement scenarios for multiple species are in great need. The previous approaches to multiple genome rearrangement problem were largely based on the breakpoint distance rather than on a more biologically accurate rearrangement (reversal) distance. Another shortcoming of the existing software tools is their inability to analyze rearrangements (inversions, translocations, fusions, and fissions) of multichromosomal genomes. This paper proposes a new multiple genome rearrangement algorithm that is based on the rearrangement (rather than breakpoint) distance and that is applicable to both unichromosomal and multichromosomal genomes. We further apply this algorithm for genome-scale phylogenetic tree reconstruction and deriving ancestral gene orders. In particular, our analysis suggests a new improved rearrangement scenario for a very difficult Campanulaceae cpDNA dataset and a putative rearrangement scenario for human, mouse and cat genomes.